Material Properties for Wire‐and‐arc Additively Manufactured Steel. Issue 4 (14th September 2022) - Tankova, Trayana; Zhu, Carlos; Branco, Ricardo
Abstract: In the era of internet and robots, sophisticated devices and real‐time simulation, the construction sector remains highly dependent on manual labor which is also the main source of delays, lack of quality, and human injuries. The rapid development in technological areas such as mechatronics, computers, sensors, programming, human interfaces, and artificial intelligence offers huge potential for modern applications. Nowadays, additive manufacturing is rapidly growing, and it could provide efficient solutions for steel construction since it can be executed in any shape and scale. There are a few solutions in additive manufacturing technologies, which can process materials and produce components. However, there is a gap in the market for capacity to link the processed material conditions and characteristics to the production parameters in real‐time. Real‐time and cognitive re‐planning of the process parameters becomes significantly important when components with large‐scale and complex shapes are considered. In steel construction, material should comply with strict requirements in terms of its strength and ductility. Hence, it is necessary to characterize the material properties before their application in construction. This paper presents material characterization for WAAM fabricated steel coupons, considering different directions with respect to the deposition direction.